2012
DOI: 10.1017/s0144686x12000578
|View full text |Cite
|
Sign up to set email alerts
|

Ageing-friendly communities and social inclusion in the United States of America

Abstract: Synthesising the social capital and ageing-friendly communities literature, this paper describes how efforts to make communities more ageing-friendly can promote social inclusion among older adults. Making existing communities more ageing-friendly involves physical and social infrastructure changes that enable older adults to pursue lifelong activities, meet their basic needs, maintain significant relationships, participate in the community in personally and socially meaningful ways, and develop new interests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
131
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(135 citation statements)
references
References 71 publications
(84 reference statements)
2
131
1
1
Order By: Relevance
“…Since the development of the concept of Age-friendly Cities by the World Health Organization (WHO), discussed further in the subsequent section, research has also emerged on this topic (Fitzgerald and Caro 2014;Greenfield et al 2015;Scharlach and Lehning 2013). Several models of an ''age-friendly community'' have been developed, not limited to urban settings (Menec and Nowicki 2014).…”
Section: Urbanization and Population Ageingmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the development of the concept of Age-friendly Cities by the World Health Organization (WHO), discussed further in the subsequent section, research has also emerged on this topic (Fitzgerald and Caro 2014;Greenfield et al 2015;Scharlach and Lehning 2013). Several models of an ''age-friendly community'' have been developed, not limited to urban settings (Menec and Nowicki 2014).…”
Section: Urbanization and Population Ageingmentioning
confidence: 99%
“…The research challenges in this area, however, are similar to those for urban health-an insufficient understanding of the actual holistic effects of physical and social environment interventions, and of the various dimensions of inequity and exclusion that affect older adults (Buffel et al 2012b;Scharlach and Lehning 2013). Thus, more local knowledge and evidence is needed on how the physical and social environment can be improved in a coherent manner to affect the health and wellbeing of older adults and other people in the community, and to prevent older adults from being systematically excluded from society.…”
Section: Urbanization and Population Ageingmentioning
confidence: 99%
“…-Employment of the elderly in suitable jobs, their encouragement to engage in social activities like educational and voluntary works should be ensured (Scharlach and Lehning, 2013). -Qualitative and quantitative development of urban equipment areas (health, education, social, cultural, commercial) in line with universal design principles and standards should be ensured (Feyzioğlu and Sayan, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…It includes the physical and social infrastructure that support daily activities through transportation, local amenities, safe and accessible housing, neighborhoods, and communities, access to social support, and opportunities to engage in meaningful activities [9,10]. There is, however, a lack of empirical studies that have examined to what extent the environmental features suggested in various frameworks apply to and affect the aging experiences of older adults in the real world.…”
Section: Empirical Assessment Of the Structure Of Age-friendly Enviromentioning
confidence: 99%